(untitled) (Journal of Educational Sciences, 2016)
In article the question about the use of information and communication and interactive educational technologies for the formation of Acmecreative qualities of future teachers of English. Achievement ACME – vertex professional and personal development possible through continuous improvement activities. Are essential creative technologies and methods of training and development. Since the development of modern society affect different spheres of human activity, including education, can be considered educational space is part of the global information and communication space. The methodology involves interactive learning, consider the following questions: a) What do we do? b) How are we going to do? b) what time is it? d) In what form will hold? The result? Foreign language,particularly English, is becoming one of the most important means of formation of Acme-creative qualities of a future teacher.